2010
DOI: 10.1631/jzus.b1000054
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and meristic variation in two congeneric archer fishes Toxotes chatareus (Hamilton 1822) and Toxotes jaculatrix (Pallas 1767) inhabiting Malaysian coastal waters

Abstract: Abstract:A simple yet useful criterion based on external markings and/or number of dorsal spines is currently used to differentiate two congeneric archer fish species Toxotes chatareus and Toxotes jaculatrix. Here we investigate other morphometric and meristic characters that can also be used to differentiate these two species. Principal component and/or discriminant functions revealed that meristic characters were highly correlated with pectoral fin ray count, number of lateral line scales, as well as number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…The fish were then deprived of food for two days and anesthetized with α-methyl quinoline (TransmoreR; Nika Trading, Puchong, Malaysia; 0.22 ml/L in 3 L of sea water as an aneasthetic medium for 10-15 min) prior to the initial measurement of total length (cm) and body weight (g). The total length was measured to the nearest 0.01 cm with a measuring board (Simon et al, 2010a) and weighed to the nearest 0.01 g (Simon et al, 2010b) using an electronic balance Model KD-300KC (Simon et al, 2012). After the starvation period, the fish were fed to satiation (Das et al, 2014b;Mazumder et al, 2015a) and offered two different diets, pellet or shrimp (four compartments for pellet and four compartments for shrimp), the leftovers after 2 min of feeding.…”
Section: Methodsmentioning
confidence: 99%
“…The fish were then deprived of food for two days and anesthetized with α-methyl quinoline (TransmoreR; Nika Trading, Puchong, Malaysia; 0.22 ml/L in 3 L of sea water as an aneasthetic medium for 10-15 min) prior to the initial measurement of total length (cm) and body weight (g). The total length was measured to the nearest 0.01 cm with a measuring board (Simon et al, 2010a) and weighed to the nearest 0.01 g (Simon et al, 2010b) using an electronic balance Model KD-300KC (Simon et al, 2012). After the starvation period, the fish were fed to satiation (Das et al, 2014b;Mazumder et al, 2015a) and offered two different diets, pellet or shrimp (four compartments for pellet and four compartments for shrimp), the leftovers after 2 min of feeding.…”
Section: Methodsmentioning
confidence: 99%
“…The successful molecular identification is valuable because of taxonomic ambiguities. Simon, Baker, Temple, and Mazlan () studied morphometric and meristic variations in two congeneric archer fishes Toxotes chatareus (Hamilton 1822) and Toxotes jaculatrix (Pallas 1767) inhabiting Malaysian coastal waters and reported that morphometric and meristic variations exist between these two species. Our morphological and genotype analysis also supported the validity of taxonomic status of B. bendelisis and B. vagra as two species from waters of Chenab river.…”
Section: Discussionmentioning
confidence: 99%
“…Since morphometric data are continuous and the meristic data are discrete, statistical analyses of both types were performed separately. Extreme outliers in the morphometric data from each region were defined as those greater than three times the inter‐quartile range, below or above the first and third quartiles and detected using a box‐plot analysis (Simon et al, ). Significant correlations between size ( L F ) and morphometric characters may accentuate such size differences (Simon et al, ) and complicate the morphometric comparisons.…”
Section: Methodsmentioning
confidence: 99%